2013
DOI: 10.3390/catal3010088
|View full text |Cite
|
Sign up to set email alerts
|

Coating SiO2 Support with TiO2 or ZrO2 and Effects on Structure and CO Oxidation Performance of Pt Catalysts

Abstract: Abstract:In this work, we studied how TiO 2 and ZrO 2 coatings enhance the CO oxidation performance of SiO 2 -supported Pt catalysts under conditions relevant to automotive emissions control. SiO 2 was coated with metal oxides TiO 2 or ZrO 2 by sol-gel method and the subsequent Pt loading was done by incipient wetness method. The prepared catalysts Pt/TiO 2 -SiO 2 and Pt/ZrO 2 -SiO 2 were compared with Pt/SiO 2 and Pt/Al 2 O 3 in fresh, sulfated, and hydrothermally aged states. The structure of the catalysts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 38 publications
3
21
1
Order By: Relevance
“…The present XAFS study suggests that the Pt nanoparticles on SiO 2 and metal-oxide-modified SiO 2 supports (i.e., TiO 2 -SiO 2 and ZrO 2 -SiO 2 ) have hemispherical and pancake shapes, respectively. Furthermore, the results demonstrate that the Pt atoms on the SiO 2 supports undergo a sufficient thermal fluctuation to form large clusters at 700 K. By contrast, the SMSI via Pt-Ti and Pt-Zr pairs prevents Pt agglomeration on TiO 2 -or ZrO 2 -incorporated SiO 2 supports at 700 K. These results are therefore consistent with prior work which showed significant improvements in the dispersion, stability and catalytic activity in oxidation reactions of Pt catalysts by incorporating TiO 2 or ZrO 2 on the surface of SiO 2 supports [34]. The in situ XAFS measurements under the redox conditions confirmed that Pt nanoparticles on TiO 2 -or ZrO 2 -incorporated SiO 2 supports could be practically used in automotive emission control catalysts or in other industrial applications below 700 K because their dispersion, shape and structural stability do not change significantly.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present XAFS study suggests that the Pt nanoparticles on SiO 2 and metal-oxide-modified SiO 2 supports (i.e., TiO 2 -SiO 2 and ZrO 2 -SiO 2 ) have hemispherical and pancake shapes, respectively. Furthermore, the results demonstrate that the Pt atoms on the SiO 2 supports undergo a sufficient thermal fluctuation to form large clusters at 700 K. By contrast, the SMSI via Pt-Ti and Pt-Zr pairs prevents Pt agglomeration on TiO 2 -or ZrO 2 -incorporated SiO 2 supports at 700 K. These results are therefore consistent with prior work which showed significant improvements in the dispersion, stability and catalytic activity in oxidation reactions of Pt catalysts by incorporating TiO 2 or ZrO 2 on the surface of SiO 2 supports [34]. The in situ XAFS measurements under the redox conditions confirmed that Pt nanoparticles on TiO 2 -or ZrO 2 -incorporated SiO 2 supports could be practically used in automotive emission control catalysts or in other industrial applications below 700 K because their dispersion, shape and structural stability do not change significantly.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in the Debye-Waller factors at 700 K by contract means that slightly less stable bonds of the Pt-Pt and Pt-Zr pairs on ZrO 2 -SiO 2 than on TiO 2 -SiO 2 . The different structural stabilities at high temperatures might explain the conversion differences observed on these two systems [34]. The coordination numbers, bond lengths, and Debye-Waller factors of Pt-O, Pt-Pt, and Ptmetals (i.e., Ti or Zr) in Pt/TiO 2 -SiO 2 and Pt/ZrO 2 -SiO 2 strongly suggest that the Pt atoms form a pancake-shape consisting of two or three Pt layers, as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The active metal, dispersed on support surfaces, plays a main role in catalyzing chemical reactions, whereas the solid support can not only disperse metal nanoparticles and assure their thermal stability, but also influence the catalytic Pt/SiO 2 performance in different ways. A series of papers concerning modified platinum catalysts have been published [13][14][15][16][17][18][19][20][21][22][23]. The addition of new components may sometimes stabilize Pt particles and produce new interfaces beneficial to the catalytic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Pure silica only presents broad diffraction peaks at 2θ values between 4-14, typical of poorly crystalline SiO2. 28 When titania is added into the system, additional diffraction peaks at 2θ values of 25, 38, 48 and 55 degrees appear, corresponding to the anatase phase of TiO2. 16a These diffraction peaks increase in intensity as the titania content increases as expected.…”
Section: Mixed Sio2:tio2 Oxides As Catalyst Supportsmentioning
confidence: 99%